Those are Your Legs: The Effect of Visuo-Spatial Viewpoint on Visuo-Tactile Integration and Body Ownership - Pozeg, Polona; Galli, Giulia; Blanke, Olaf (Frontiers in Psychology, 2015)
Experiencing a body part as one’s own, i.e. body ownership, depends on the integration of multisensory bodily signals (including visual, tactile, and proprioceptive information) with the visual top-down signals from peripersonal space. Although it has been shown that the visuo-spatial viewpoint from where the body is seen is an important visual top-down factor for body ownership, different studies have reported diverging results. Furthermore, the role of visuo-spatial viewpoint (sometime also called first-person perspective) has only been studied for hands or the whole body, but not for the lower limbs. We thus investigated whether and how leg visuo-tactile integration and leg ownership depended on the visuo-spatial viewpoint from which the legs were seen and the anatomical similarity of the visual leg stimuli. Using a virtual leg illusion, we tested the strength of visuo-tactile integration of leg stimuli using the cross-modal congruency effect (CCE) as well as the subjective sense of leg ownership (assessed by a questionnaire). Fifteen participants viewed virtual legs or non-corporeal control objects, presented either from their habitual first-person viewpoint or from a viewpoint that was rotated by 90° (third-person viewpoint), while applying visuo-tactile stroking between the participants legs and the virtual legs shown on a head-mounted display. The data show that the first-person visuo-spatial viewpoint significantly boosts the visuo-tactile integration as well as the sense of leg ownership. Moreover, the viewpoint-dependent increment of the visuo-tactile integration was only found in the conditions when participants viewed the virtual legs (absent for control objects). These results confirm the importance of first person visuo-spatial viewpoint for the integration of visuo-tactile stimuli and extend findings from the upper extremity and the trunk to visuo-tactile integration and ownership for the legs.